Diabetes Mellitus Increases the Risk of Hepatocellular Carcinoma After Direct-Acting Antiviral Therapy: Systematic Review and Meta-Analysis - Váncsa, Szilárd; Németh, Dávid; Hegyi, Péter; Szakács, Zsolt; Farkas, Ádám; Kiss, Szabolcs; Hegyi, Péter Jenő; Kanjo, Anna; Sarlós, Patrícia; Erőss, Bálint; Pár, Gabriella (Frontiers in Medicine, 2021)
Background: Hepatitis C virus (HCV)-infected patients treated with direct-acting antivirals (DAAs) are still at risk of developing hepatocellular carcinoma (HCC) after sustained virologic response (SVR). This study aimed to investigate the role of diabetes mellitus (DM) as a potential predictive risk factor in developing de novo HCC in HCV-infected patients after DAA treatment. Methods: This study was registered on PROSPERO under registration number CRD42021230457. We performed a systematic search in four medical databases from inception through November 3rd, 2020. Studies were eligible if they reported on HCV-infected patients treated with DAAs and compared the frequency of de novo HCC in patients with and without DM. We calculated pooled odds ratios, unadjusted (UHR), and adjusted hazard ratios (AHR) with 95% confidence intervals (CIs) in meta-analysis. Results: We included 30 articles in our systematic review and meta-analysis. DM proved to be a significant risk factor of HCC in DAA-treated HCV patients in unadjusted (UHR = 1.44, CI: 1.15–1.79) and adjusted analyses (AHR = 1.31, CI: 1.06–1.62). In the group of patients achieving SVR after DAA therapy, DM increased the risk of HCC in unadjusted (UHR = 1.3, CI: 1.09–1.51) analysis; however, in adjusted results, the risk was non-significant (AHR = 1.07, CI: 0.89–1.28). In patients with advanced liver fibrosis, DM was a risk factor for HCC in adjusted (AHR = 1.36, CI: 1.03–1.8), but not in unadjusted analysis (UHR = 1.11, CI: 0.8–1.42). Conclusions: DM is an independent risk factor of de novo HCC after DAA treatment in HCV-infected patients. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=230457, identifier: CRD42021230457.